1990
DOI: 10.1002/pola.1990.080280802
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and kinetic approaches for the basic type of MgCl2‐supported high yield catalysts

Abstract: N u m z u 41 0, Japan Synopsis Thermal analysis in combination with infrared spectroscopy was applied to investigate the states of ethylbenzoate (EB) and TiC1, in the simple type of the MgC1,-supported high-yield catalysts. A further attempt was made to evaluate kinetic parameters in the initial stage of propylene polymerization (i Is) by a stopped flow method. The catalysts employed in the present study were prepared by co-grinding MgC1, and TiCl, . EB complex. Thermal analysis and infrared spectroscopy showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…It suggests EB interacts directly only with MgCl 2 and there is no direct reaction between EB and TiCl 4 in catalyst A. This result is in agreement with the results obtained by Terano [12,13] and Yang [14] .…”
supporting
confidence: 93%
“…It suggests EB interacts directly only with MgCl 2 and there is no direct reaction between EB and TiCl 4 in catalyst A. This result is in agreement with the results obtained by Terano [12,13] and Yang [14] .…”
supporting
confidence: 93%
“…It was demonstrated that an internal donor was strongly bound to the MgCl 2 support and did not interact with adsorbed TiCl 4 . [12,13] In general, donors block aspecific sites on MgCl 2 surface selectively to increase the isospecific Ti dinuclear species and coadsorb with Ti species to transform aspecific sites into isospecific sites. [14][15][16] Even though many scientists explained isospecificity increase by the existence of donors according to these results, the effects of donors are considered to be more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…IR spectroscopy has been extensively applied to Ziegler-Natta catalysts [17]. With regard to propylene polymerization catalysts, most of the work has focused on the spectral changes in the m C=O of the internal aromatic ester in various stages of catalyst preparation [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%